Serodiagnosis of Toxocara Antibodies Among infants and pregnant women Suspected of Ocular or Visceral Toxocariasis Using Two Types ELISA Antigens [TEE & TEX ] - Issa, Raga M (Gezira Journal of Health Sciences; Vol 3 No 2 (2007), 2007)
The diagnosis of toxocariasis depends heavily on immunological tests because parasites may be few in the tissue of those infected and, unless situated in an organ such as the eye, may be difficult or impossible to locate. In general, patients with ocular toxocariasis have serum anti- T canis antibody titres that are significantly lower than those with visceral toxocariasis. An enzyme linked immunosorbent assay (ELISA) using T canis embryonated egg antigen (TEE) and (TEX) were used for diagnosis of toxocariasis. This assay showed a high degree of sensitivity and specificity. Aim of work, diagnosis of asymptomatic toxocariasis in infants before two years old and suspected infection in pregnant women by ELISA with comparison between two antigens TEE & capture TEX. This work was done between 8/2005 and 4/2006. Specimens of serum collected from 79 infants (apparent healthy ) aged between 4 weeks to 30 moths (51 females and 28 males ) Also, 28 specimens of serum collected from asymptomatic pregnant women aged between 18-32 years old and their infants (28 )(17 females and 11 males) at the same age of infants above . The baseline laboratory studies that were done included WBCs, differential count and circulating eosinophil count. Examination of faeces for ova and any parasites. Serodignosis by ELISA using two of antigens , Toxocara canis embryonated egg antigen ( TEE ) and Toxocara canis antigen capture ELISA. Results , Toxocara antibodies found in 7 &12 pregnant women serum when tested by TEE & capture TEX ELISA respectively. The serum samples of infants (28) which taken from infant's pregnant mothers given positive for Toxocara antibodies 3/28 and 7/28 when tested by TEE ELISA and capture TEX ELISA respectively. Active ocular toxocariasis diagnosed in one mother only in left eye. All in active ocular toxocariasis diagnosed by capture TEX ELISA except one baby's serum only diagnosed by TEE ELISA . In conclusion, the capture TEX ELISA was better able to discriminate between positive and negative samples than TEE ELISA. In addition, testing samples by both capture TEX ELISA and TEE ELISA. Toxocariasis should be given more attention and that the ophthalmologists should be more aware of this disease-especially in children and young adults-and should more often include toxocariasis in the differential diagnosis of the ocular diseases.